Analisis Implementasi Kurikulum Merdeka di Sekolah Dasar - Qiftiyah, Maratul; Atika Nur Hidayati (Al Banin : Jurnal Ilmiah Pendidikan Dasar, 2024)
Independent curriculum is an education policy that aims to provide schools with flexibility to develop learning that is more in line with students' needs. This study analyzes the implementation of the independent curriculum at SDN 1 Sumber Agung, focusing on implementation strategies, challenges faced, and its impact on the learning process. The approach used is descriptive qualitative, with data collection through interviews, observations, and document analysis. The results of the study indicate that SDN 1 Sumber Agung has implemented the independent curriculum with a thematic approach, project-based learning, and formative assessment. However, the challenges faced include the lack of teacher understanding of the independent curriculum concept, limited learning resources, and resistance from several parties to changes in learning practices. Nevertheless, the independent curriculum has a positive impact, especially in increasing teacher creativity, student engagement, and the relevance of learning to the needs of the times. This study also identified that the success of implementation is highly dependent on effective teacher training, support from the principal, and the active involvement of all related parties. Therefore, efforts are needed to strengthen teacher competence and ongoing mentoring so that the implementation of the independent curriculum can be more optimal.